EKSPLORASI HAMBATAN PENYUSUNAN LAPORAN KEUANGAN UMKM MELALUI FOCUS GROUP DISCUSSION (FGD) PADA UMKM PROVINSI SUMATERA UTARA - Yenni Arfah; Yochi Elanda (Smart Education, 2026)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, including in North Sumatra Province. However, most MSMEs still face challenges in preparing financial reports that comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This study aims to explore in depth the obstacles faced by MSMEs in North Sumatra Province in preparing financial reports. The research method used is a qualitative approach with a Focus Group Discussion (FGD) technique involving 20 MSME actors as participants from various sectors across 7 regencies/cities in North Sumatra Province. The data were analyzed using thematic analysis techniques. The results identified five main themes of obstacles: (1) low accounting literacy and understanding, (2) limited human resources, (3) financial recording practices that remain simple and manual, (4) the absence of separation between personal and business finances, and (5) lack of socialization and assistance regarding SAK EMKM. This study contributes by providing a mapping of factual obstacles that can serve as a basis for formulating more targeted intervention policies to improve the capacity of MSMEs in preparing financial reports in North Sumatra. Keywords: Financial Report Preparation Barriers, MSMEs, SAK EMKM, Focus Group Discussion, North Sumatra. Abstrak: Usaha Mikro, Kecil, dan Menengah (UMKM) merupakan tulang punggung perekonomian Indonesia, termasuk di Provinsi Sumatera Utara. Namun, sebagian besar UMKM masih menghadapi kendala dalam menyusun laporan keuangan yang sesuai dengan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM). Penelitian ini bertujuan untuk mengeksplorasi secara mendalam hambatan-hambatan yang dihadapi UMKM di Provinsi Sumatera Utara dalam penyusunan laporan keuangan. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik Focus Group Discussion (FGD) yang melibatkan 20 pelaku UMKM sebagai partisipan dari berbagai sektor pada 7 Kabupaten / Kota Provinsi Sumatera Utara. Data dianalisis menggunakan teknik analisis tematik. Hasil penelitian mengidentifikasi lima tema utama hambatan: (1) rendahnya literasi dan pemahaman akuntansi, (2) keterbatasan sumber daya manusia, (3) pencatatan keuangan yang masih sederhana dan manual, (4) belum adanya pemisahan keuangan pribadi dan usaha, serta (5) kurangnya sosialisasi dan pendampingan SAK EMKM. Penelitian ini memberikan kontribusi berupa pemetaan hambatan faktual yang dapat menjadi dasar bagi perumusan kebijakan intervensi yang lebih tepat sasaran dalam meningkatkan kapasitas penyusunan laporan keuangan UMKM di Sumatera Utara. Kata kunci: Hambatan Penyusunan Laporan Keuangan, UMKM, SAK EMKM, Focus Group Discussion, Sumatera Utara